2006
DOI: 10.1002/anie.200600060
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Locomotion

Abstract: Research into the autonomous motion of artificial nano- and microscale objects provides basic principles to explore possible applications, such as self-assembly of superstructures, roving sensors, and drug delivery. Although the systems described have unique propulsion mechanisms, motility in each case is made possible by the conversion of locally available chemical energy into mechanical energy. The use of catalysts onboard can afford nondissipative systems that are capable of directed motion. Key to the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
486
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(497 citation statements)
references
References 56 publications
8
486
0
3
Order By: Relevance
“…One of the successful strategies recently developed includes conversion of chemical energy into mechanical work of propulsion. In the initial pioneering experiments, Paxton et al [154,155] observed the autonomous motion of platinumgold nanorods (370 nm diameter and 2 mm length) in a hydrogen peroxide solution. The exact mechanism for the propulsion of these micro-swimmers is still a developing area of research and various models have been proposed.…”
Section: Janus and Patchy Particles In Chemical Environmentsmentioning
confidence: 99%
“…One of the successful strategies recently developed includes conversion of chemical energy into mechanical work of propulsion. In the initial pioneering experiments, Paxton et al [154,155] observed the autonomous motion of platinumgold nanorods (370 nm diameter and 2 mm length) in a hydrogen peroxide solution. The exact mechanism for the propulsion of these micro-swimmers is still a developing area of research and various models have been proposed.…”
Section: Janus and Patchy Particles In Chemical Environmentsmentioning
confidence: 99%
“…Directly moving micro-/nano-objects is of great importance in numerous potential applications, such as intelligent drug-delivery, smart nanomachinery and nanoscale assembly, [1][2][3] which require the design and fabrication of powerful micro-/nanoengines to overcome the Brownian motion and viscous forces that become significant at such small size scales. 4 Such engines, which have been produced by nature through millions of years of evolution, have the ability to convert chemical energy to mechanical energy.…”
Section: Introductionmentioning
confidence: 99%
“…Several artificial systems that exhibit self-motion under conditions of chemical nonequilibrium have been studied experimentally [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and theoretically [16][17][18][19] under almost isothermal conditions.…”
Section: Introductionmentioning
confidence: 99%